Bureaucratic Reform at Bandung Departement of Culture and Tourism in the New Public Service Perspective - Ahmad Azka Nubala; Entang Adhy Muhtar; Raden Ahmad Buchari (Universitas Padjadjaran, 2024)
This study purposed to analyze the application of New Public Service principles in bureaucratic reform through bureaucratic simplification policies at the Culture and Tourism Office of Bandung City. The research was conducted using descriptive qualitative methods. The data sources were collected through interviews, observations, and document studies. The results showed that the Department of Culture and Tourism of Bandung City has implemented New Public Service principles, such as: serving citizens, not customers; prioritizing public interests; respecting citizenship values; thinking strategically and acting democratically; multidimensional accountability; serving and empowering, leading; and respecting people, not just productivity. The application of these principles can be seen in programs such as online data and interview services, Bandung Creative Hub, intellectual property registration, collaboration with tourism stakeholders, art environment legalization programs, tax incentives for cultural heritage, and support for local art communities. This study concludes that the bureaucracy simplification policies of the Department of Culture and Tourism of Bandung have been implemented by promoting democratic values, public participation, and community service orientation, in line with the principles of New Public Service.